The Relationship Between Hypertension and Quality of Life in Chronic Kidney Disease Patients Undergoing Hemodialysis at Sentra Medika Hospital, Cikarang, Bekasi Regency 2025 - Sinaga, H, J; Nadzia, S; Sari Retno, A, P (Jurnal Multidisiplin Sahombu, 2025)
Chronic Kidney Disease (CKD) has emerged as one of the most prominent causes of death and suffering in the 21st century. This study aims to indetify the relationship between hypertension and quality of life in patients with chronic kidney disease undergoing hemodialysis at the Sentra Medika Cikarang Hospital 2025. This research method is quantitative analytical with a cross sectional study design. The populatin in this study was 185 patients with chronic kidney disease, with samples being selected using the Slovin formula.so that a sampel of 72 respondent with kidney failure undegoing hemodialysis. The measuring instrumnet used in this study was a questionnaire that explored the characteristics of respondent, hypertension and the WHOQOL questionnaire to measure quality of life. The analysis used univariate and bivariat using the spearman rank test. Based on this research, the resuts of bivariate analysis using the spearman rank test, there was a significant relationship (p-value = 0,000) which was strong and in the same direction between the variables of hypertension risk factors and the quality of life of patients with chronic kidney disease. The Suggestions based on this research are expected for further researchers to be able to develop this study, by looking for the relationship of effectiveness between other independent variables and the quality of life in patients with chronic kidney disease, using methods and research design other than quantitative analytics, as well as deeper analysis for the development of new scientific knowledge on the quality of life of patients with chronic kidney disease.